Correction: Synthesis and properties of clickable A(B-b-C)20 miktoarm star-shaped block copolymers with a terminal alkyne group. Issue 21 (7th June 2015) - Huang, Bing; Chen, Min; Zhou, Shuxue; Wu, Limin
<x xml:space="preserve">Abstract</x> Correction for 'Synthesis and properties of clickable A(B-b-C)20 miktoarm star-shaped block copolymers with a terminal alkyne group' by Bing Huang et al., Polym. Chem., 2015, DOI: 10.1039/c5py00338e.